The influence of genetic variation in PSIP1 on HIV-1 infectivity in black South Africans - Gentle, Nikki (My University, 2010)
Genetic variation plays an important role in determining an individual’s susceptibility to infectious disease. PSIP1 encodes LEDGF/p75, which stably associates with the core domain of HIV-1 integrase via a highly-conserved integrase binding domain (IBD) located in its C-terminal. Through this interaction, the protein tethers HIV-1 IN to chromosomes at sites corresponding to regions of high LEDGF/p75-mediated transcription. Genetic variation within PSIP1 was identified and characterized in black South Africans to establish whether variation in this influences an individual’s susceptibility to HIV infection. PCR assays were designed to amplify regions within the upstream non-coding region, IBD and DNA-binding domains of the gene and selected polymorphisms were then genotyped using allele-specific PCR, RFLP-PCR and Pyrosequencing™ assays. Three insertion-deletion (indel) and eight single nucleotide polymorphisms (SNP) where identified through sequencing. Four of the SNPs had been recorded previously, while the seven other polymorphisms had not and appear to be unique to our population. Differences in allelic and genotypic frequencies where found between the various ethnic groups represented in this study, which were reflected in the underlying haplotype structure within this gene, suggesting that genetic substructure exists within the black South African population. Differences in allele and genotype frequencies were also seen between HIV+ individuals and the general population. Thus variation within PSIP1 may influence an individual’s susceptibility to HIV-1 infectivity and/or rate of disease progression.